Bacteriophage T4-Directed DNA Synthesis in Toluene-Treated Cells - Dicou, Liana (1973)
DNA synthesis has been studied in T4-infected Escherichia coli cells made permeable to nucleotides by treatment with toluene. The rate of incorporation of labeled deoxyribonucleoside triphosphates into DNA at various times after infection is proportional to the in vivo rate. This in vitro incorporation is dependent on all four deoxyribonucleoside triphosphates (5-hydroxymethyldeoxy-cytidine triphosphate can substitute for dCTP) and Mg(2+). It is stimulated by rATP, partially inhibited by pancreatic DNase, and abolished by N-ethylmalei-mide and 1-β-d-arabinofuranosylcytosine triphosphate. T4 amber DO (DNA negative) and temperature-sensitive DO mutants under nonpermissive conditions of infection fail to induce DNA synthesis in vitro. The synthesizing activity is intracellular and the DNA product is exclusively T4 DNA. The in vitro synthesis proceeds in a discontinuous manner involving synthesis and subsequent joining of small DNA fragments (about 10S in alkaline sucrose gradients) into larger molecules predominantly one-half the length of mature T4 DNA. No restriction of C-containing or nonglucosylated HMC-containing T4 DNA product is observed in this system.